"New Normal" implications for global talent in the wake of economic nationalism and slowdown. (9th April 2022) - Showkat, Saloome; Wani, Tahir; Kaur, Jaspreet
Abstract: As a result of global economies' protectionist policies, followed by economic nationalism and a downturn, there is a shortage of talent with the requisite skills, knowledge, and abilities to meet the contingencies amid COVID‐19. The recent developments have necessitated multinational businesses to manage their talent in a new international business context. Therefore, the purpose of this paper is to explore the implications of the "New Normal" for global talent which is manifested by economic nationalism and slowdown. This study used an inductive method to qualitative research, conducted in‐depth interviews with 28 top executives from multinational corporations. The implications for the global talent emerged from the current study as skill enhancement based on the emerged business model; training and development pertinent to new responsibilities and activities; adaptability to changes in the macroenvironment; emphasis on employee proactivity, experimentation, and risk‐taking; emphasis on hyperspecialization to take on contract positions; global talent needs to participate in remote learning; global talent must emphasize on mental health issues; and registering in talent exchange programs to fill talent skill shortages.